The Students' Interest and Motivation in Learning English of Seventh Grade Students at MTs An-Nur 1 Bululawang: English - Moch. Arief Naszar Arief; Tyas Alhim Mubarok; Ahmad Saifuddin (Journal of English Development, 2023)
The purpose of this study was to determine the level of student interest in learning and motivation towards learning English at MTs An-Nur Bululawang. The type of research used by researchers is qualitative research, namely research that focuses on in-depth observation of a problem. The method used is field research, which is a data collection method that aims to observe, interact, and understand people when they are in the natural environment. In the world of education, interest and motivation are needed because it includes an attitude or encouragement that is carried out continuously in order to achieve something that is desired. According to the results of the analysis above, MTs An-Nur Bululawang students have high enthusiasm to take part in learning English at school. They try to answer the teacher's questions and ask the teacher if there is material that they don't understand. However, when they are given assignments from the teacher, they prefer to just copy their friends rather than do it themselves. they also don't really review English lessons at Islamic boarding schools. one of the factors that influence them are individual students, the school environment, and the pesantren environment.